Extract From Tetrastigma hemsleyanum Leaf Alleviates Pseudomonas aeruginosa Lung Infection: Network Pharmacology Analysis and Experimental Evidence - Tian-ling Lou; Tao Ji; Xin Peng; Wei-wei Ji; Li-xia Yuan; Juan Wang; Shi-min Li; Shun Zhang; Qiao-yun Shi (Frontiers Media S.A., 2021)
Tetrastigma hemsleyanum Diels & Gilg (T. hemsleyanum) has attracted much attention due to its ability on pneumonia, bronchitis, and immune-related diseases, while its functional components and underlying mechanism of action on pneumonia have not been fully elucidated. Herein, we used a systematic network pharmacology approach to explore the action mechanism of T. hemsleyanum leaf in the treatment of pneumonia. In this study, the results of network pharmacology demonstrated that there were 34 active components and 80 drug-disease targets in T. hemsleyanum leaf, which were strongly in connection with signal transduction, inflammatory response, and the oxidation-reduction process. Subsequently, a mouse model of pneumonia induced by Pseudomonas aeruginosa (P. aeruginosa) was established to validate the predicted results of network pharmacology. In the animal experiments, aqueous extract of T. hemsleyanum leaf (EFT) significantly attenuated the histopathological changes of lung tissue in P. aeruginosa-induced mice and reduced the number of bacterial colonies in BALFs by 96.84% (p < 0.01). Moreover, EFT treatment suppressed the increase of pro-inflammatory cytokines IL-17, IL-6, and TNF-α in lung tissues triggered by P. aeruginosa, which led to the increase of Th17 cells (p < 0.05). High concentration of EFT treatment (2.0 g/kg) obviously increased the anti-inflammatory cytokine levels, accompanied by the enhancement of Treg proportion in a dose-dependent manner and a notable reversal of transcription factor RORγt expression. These findings demonstrated that network pharmacology was a useful tool for TCM research, and the anti-inflammatory effect of EFT was achieved by maintaining Th17/Treg immune homeostasis and thereby suppressing the inflammatory immune response.